Surface properties of sediments from two Argentinean reservoirs and the rate of phosphate release - Borgnino, L. (2006)
This article reports the surface properties (electrophoretic mobility, surface charge and specific surface area (SSA)), and phosphate release rates of sediments from two Argentinean reservoirs. Even though sediments are a heterogeneous mixture of minerals with different charging behavior, electrophoresis reveals that all sediment particles are negatively charged in the pH range 3-9. Iron and aluminum oxides, which usually carry a net positive charge at low pH, seem to be forming aggregates with negatively charged minerals and/or carrying a net negative charge due to the presence of organic matter. The phosphate release rate increased by increasing pH and temperature, and depended linearly on the SSA of the sediments. These data, together with the high activation energy of the process, indicate that the rate-controlling process is a chemical reaction occurring at the solid-water interface, and not a diffusion process. The rate-controlling step seems to be the breaking of bonds between phosphate and surface groups, breaking that should be preceded by one or more deprotonation steps at the surface and favored by electrostatic repulsion between the negative charge surface and the phosphate anion.